Effect of the Cooling Process on the Structure and Charge/Discharge Cycling Performance in Li[Li0.20Mn0.58Ni0.18Co0.04]O2 Li-Rich Solid-Solution Layered Oxide Cathode Materials for Li-Ion Battery. (19th June 2018) - Nomura, Fumihiro; Tanabe, Toyokazu; Gunji, Takao; Matsumoto, Futoshi
Abstract : In this study, the cooling conditions for calcinated lithium-rich solid-solution layered oxide materials (LLOs) of Li[Li0.20 Mn0.58 Ni0.18 Co0.04 ]O2 were examined to determine the cooling conditions and crystal structure that produce a high and stable charging/discharging cathode capacity for LLOs. The crystal structures of LLO samples which were quenched in liquid nitrogen, cooled in air at room-temperature and at a controlled cooling rate of 100°C h -1 in a furnace were evaluated via powder X-ray diffractometry ( p XRD) experiments and transmission electron microscopy (TEM). The evaluated crystal structures of the LLOs were related to the charging/discharging cycle cathode performance.